Giant magnetoresistance in different multilayer system of CoCu and Co/Ag systems [compact disc] - 318274 Mussak Datulaqma Md. Mustam (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains (Fizik Bahan)) - Universiti Teknologi Malaysia, 2006